Crafting Poetic Imagery: The Role of Dialect in Documentary Filmmaking Through a Chinese Lens - Chen, Chen (European Centre for Minority Issues, 2026)
This article examines how Zhuji dialect operates as a generative aesthetic system within contemporary documentary filmmaking through a Chinese cinematic lens. Focusing on the short documentary Little Potato, the paper argues that dialect functions beyond spoken communication or regional realism, becoming a poetic mechanism that shapes cinematic rhythm, imagery, memory, and emotional atmosphere. Through tone, cadence, fragmentation, and oral texture, Zhuji dialect actively informs the film’s audiovisual language and contributes to the construction of poetic imagery. Drawing from practice-led research, the article reflects on the relationship between dialect, domestic space, and observational filmmaking. The study briefly engages with the Xiang system in Chinese aesthetics, where sensory images and symbolic associations generate emotional and philosophical meaning beyond literal representation. Within this framework, Zhuji dialect functions as an embodied cultural image that evokes memory, intimacy, and temporality.
Keywords: poetic documentary; practice-led artistic research; the Xiang system; Zhuji dialect